A silicon nanomembrane platform for the visualization of immune cell trafficking across the human blood–brain barrier under flow - Mossu, Adrien (J Cereb Blood Flow Metab, 2018)
Here we report on the development of a breakthrough microfluidic human in vitro cerebrovascular barrier (CVB) model featuring stem cell-derived brain-like endothelial cells (BLECs) and nanoporous silicon nitride (NPN) membranes (µSiM-CVB). The nanoscale thinness of NPN membranes combined with their high permeability and optical transparency makes them an ideal scaffold for the assembly of an in vitro microfluidic model of the blood–brain barrier (BBB) featuring cellular elements of the neurovascular unit (NVU). Dual-chamber devices divided by NPN membranes yield tight barrier properties in BLECs and allow an abluminal pericyte-co-culture to be replaced with pericyte-conditioned media. With the benefit of physiological flow and superior imaging quality, the µSiM-CVB platform captures each phase of the multi-step T-cell migration across the BBB in live cell imaging. The small volume of <100 µL of the µSiM-CVB will enable in vitro investigations of rare patient-derived immune cells with the human BBB. The µSiM-CVB is a breakthrough in vitro human BBB model to enable live and high-quality imaging of human immune cell interactions with the BBB under physiological flow. We expect it to become a valuable new tool for the study of cerebrovascular pathologies ranging from neuroinflammation to metastatic cancer.